Predictive role of perfectionism on academic achievement life satisfaction - Göç, Zeynep. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The main aim of this study was to investigate the predictive role of perfectionism on the level of achievement and life satisfaction. In this context, the impact of various perfectionism dimensions (excessive concern over mistakes, high personal standards, doubts about actions, need for organization, high parental expectations and excessive parental criticism), adaptive, maladaptive or overall perfectionism on academic achievement, various life satisfaction dimensions (friend, family, school, environment and self) and overall life satisfaction of male and female high school students was explored. The study was carried out in 3 high schools in İstanbul and 181, 10th grade students who were selected from these schools formed the sample of the study. The Turkish form of Frost Multidimensional Perfectionism Scale, the Turkish form of Multidimensional Students' Life Satisfaction Scale and demographic information form were administered to participants. Multiple regression analyses revealed that excessive criticism showed a general maladaptive pattern and predicted academic achiement, fried satisfaction and family satisfaction negatively. Adaptive perfectionism, on the other hand, made a positive contribution to the overall life satisfaction and school satisfaction. Relying on these results, it can be concluded that this study confirmed the importance of the parenting style and the quality of parent-child relationships in terms of predicting life satisfaction of adolescents and the importance of adaptive perfectionism (the combined effect of having high personal standards and of being ordered and organized) for satisfaction with life and its dimensions.
Keywords: Perfectionism (Personality trait).; Academic achievement.